2012
DOI: 10.1007/s00134-012-2519-y
|View full text |Cite
|
Sign up to set email alerts
|

Does patient volume affect clinical outcomes in adult intensive care units?

Abstract: The results indicate that outcomes of certain subsets of ICU patients--especially those on mechanical ventilation, high-risk patients, and patients with severe sepsis--are better in high volume centres within the constraints of risk adjustments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 57 publications
(165 reference statements)
2
33
0
Order By: Relevance
“…As suggested by Chieregato and colleagues and demonstrated elsewhere, regional networking and collaboration provides a mechanism for shared service improvement and quality assurance [24], potentially levelling differences in outcome [10]. This is consistent with the successful experience of critical care networks in many parts of England and Wales since 2001.…”
Section: Underlying Principlessupporting
confidence: 71%
See 1 more Smart Citation
“…As suggested by Chieregato and colleagues and demonstrated elsewhere, regional networking and collaboration provides a mechanism for shared service improvement and quality assurance [24], potentially levelling differences in outcome [10]. This is consistent with the successful experience of critical care networks in many parts of England and Wales since 2001.…”
Section: Underlying Principlessupporting
confidence: 71%
“…A recent UK retrospective cohort study showed a positive volume-outcome relationship in 104 844 admissions requiring mechanical ventilation in general critical care units [9]. Volume-outcome benefits may be influenced by diagnostic subgroup and severity [9,10], indicating a possible rationale for selective escalation. Conversely, a study of 5131 nonsurgical admissions to US Veterans Administration hospitals, with shared organisational and governance attributes, showed unifomity of outcomes independent of case volume, suggesting that evidencebased practice and standardisation of staffing care may mitigate variation by unit size [11].…”
Section: Should Regional Icus Be a Primary Goal?mentioning
confidence: 99%
“…Because ANNs can be trained with data acquired in specific clinical contexts, they can consider local expertise, Table 4 Comparison of 1000 pairs of data sets from logistic regression and the multilayer perceptron (MLP) and radial basis function (RBF) models in predicting in-hospital mortality postoperative outcome, is crucial. Kanhere et al 22 applied a systematic search strategy to identify published studies of volume-outcome relationships in adult ICU patients. They concluded that, under the constraint of risk adjustment, certain subsets of ICU patients such as those requiring mechanical ventilation or those with severe sepsis or other high-risk conditions tend to have better outcomes in highvolume hospitals than in low-volume hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that, under the constraint of risk adjustment, certain subsets of ICU patients such as those requiring mechanical ventilation or those with severe sepsis or other high-risk conditions tend to have better outcomes in highvolume hospitals than in low-volume hospitals. 22 Treatment outcomes clearly depend not only on management of patients, but also on the skill and experience of individual physicians. Meanwhile, high-volume physicians in high-volume hospitals are most likely to achieve good outcomes for patients because such physicians are usually assisted by highly skilled and interdisciplinary care teams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation